Evaluating communication skills of undergraduate healthcare students in Malaysia - Ruslan, Rusila; Abdullah, Siti Nur Dini (Palembang MediRose Publisher, 2025)
Background: Effective communication is a cornerstone of safe and high-quality patient care, influencing clinical outcomes, patient satisfaction, and trust in healthcare providers. Inadequate communication skills among healthcare professionals have been linked to preventable adverse events, delayed treatment, and diminished therapeutic relationships. Early development of communication competencies during undergraduate training is therefore essential to prepare future healthcare professionals for patient-centered practice. Objective: This study aimed to assess the communication skills of undergraduate healthcare students at the International Islamic University Malaysia (IIUM), Kuantan, Pahang, and to examine whether demographic factors influence these skills. Methods: A descriptive cross-sectional survey was conducted from March to April 2024 among 197 undergraduate students from medicine, nursing, pharmacy, dentistry, and allied health faculties. Communication skills were measured using the validated Self-Efficacy 12 (SE-12) questionnaire. Fisher’s exact and chi-square tests were applied to evaluate associations between communication skills and demographic variables including age, gender, year of study, and faculty affiliation.Results: More than half of the participants (54.8%) demonstrated good communication skills, whereas 45.2% exhibited poor skills, reflecting the need for curriculum strengthening. No significant associations were observed between communication skills and demographic characteristics (p?>?0.05), suggesting that factors beyond sociodemographics—such as teaching methods, learning opportunities, and personal experiences—may be more influential. Conclusion: Communication proficiency among healthcare undergraduates is not determined by demographic factors. Integrating comprehensive, experiential communication training into healthcare curricula could enhance competencies, improve patient safety, and foster more effective provider-patient relationships. Future research should explore additional determinants to guide targeted educational interventions.